Analisis Kadar Timbal (Pb) Dalam Daging Kerang Bakau (Polymesoda erosa) Dan Kerang Darah (Anadara granosa) Di Perairan Salule Pasangkayu Sulawesi Barat - Rahmawati, Rahmawati; Hamzah, Baharuddin; Nuryanti, Siti (Universitas Tadulako, 2015)
Bivalve os one marine animals that can efficiently accumulate to heavy metal. This is due to they livein the base layer of the sediment in the aquatic and they are moving very slowly. Therefore, it has beendone a research about the analysis of consentration of lead (Pb) in the bivalve polymesoda erosa sp andthe bivalve anadara granosa at the aquatic of Salule Pasangkayu West Sulawesi has been reported byusing direct spectro. The research’s aim was to analyze concentration of Pb as heavy metal in the bivalvepolymesoda erosa and the anadara granosa sp, The results obtained that concentration of Pb at muddyplaces was higher than at sandy area. Level of Pb showed that Pb exceeds quality standard in both clamswhere in the blood clam was 3.75 mg/Kg and 3.857 in dry weight, while the Mangrove calm showedthe result of 5,00 mg/Kg and 5.25 mg/Kg in dry weight.